Intramedullary Spinal Cord Cavernoma: A Case Report and Literature Review - Widjaya, Ingrid A; Yunus, Yesaya; Wahjoepramono, Eka Julianta; July, Julius (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Spinal cord intramedullary cavernous malformation (SICM) is kind of rare vascular disease, and the therapeutic strategy is still under debate. Cavernous malformation (CM) can be found throughout the central nervous system (CNS) but only rarely occur within the spinal cord. The purpose of this article is to describe natural history, clinical presentation and outcome of SICM case which treated surgicallyCase Presentation: A 70-year-old healthy woman presented with lower extremity weakness. A posterior laminectomy was performed, and a diagnosis of intramedullary spinal cord cavernous malformation was established. Neurological improvement was seen in one month after surgeryConclusion: Intramedullary CM is a rare disease but one with significant consequences if not managed appropriately. whenever safely feasible, gross total resection is suggested, to prevent rebleeding and further worsened of neurological deficit.